Sabellaria nanella (Sabellariidae): From solitary subtidal to intertidal reef-building worm at Monte Hermoso, Argentina (39°S, south-west Atlantic) - Bremec, Claudia Silvia (2013)
This contribution reports the first record of intertidal reefs built by the sabellariid worm Sabellaria nanella in the lower intertidal at Monte Hermoso beach, Argentina (39°S). All previous records of S. nanella in the study area correspond to solitary individuals from shallow subtidal depths in coastal environments, while the present findings refer to well established reefs on stony rocks. Worms sort medium size sand grains to build the reefs, which contain higher amount of organic matter than the surrounding sediments. Size structure of worms shows multiple size cohorts that include recent recruits and mature adults. Many invertebrates, i.e. various annelids, arthropods, molluscs, nemerteans and nematodes, are the frequent organisms living within the reef, some of them already recorded in the area. The presence of intertidal reefs of S. nanella indicates that the species has plasticity to adapt to environments with different physical conditions (subtidal–intertidal areas).